Properties & Characterisation Of The Halochromic CMC-PEG Hydrogel Film - Samsul Baharin, Massara (Universiti Sains Malaysia, 2022)
The aim of this study is to fabricate the properties and characterization of the halochromic CMC-PEG hydrogel film. The present work describes the production of carboxymethylcellulose (CMC) - polyethylene glycol (PEG) films using citric acid as a non-toxic and natural component which acts as a crosslinking agent and chlorophenol red (CPR) as a dye that monitors pH-variations through a colour change of halochromic behaviour. The solution-casting process was used to create the composite hydrogel films. The material's surface was analysed before and after crosslinking using physiochemical, morphological, and mechanical methods. This method would assist in determining whether the hydrophilicity, roughness, and rheological properties of the hydrogel films are improved by the chemical treatment of the cellulose hydrogel. Af ter their synthesis, all films were then characterized through Halochromic Responsive Test, Colour Analysis, Tensile Test, Swelling Test, Fourier-Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscope (SEM). This instrument analysis allows evaluation of the mechanical properties, glass transition temperature, melting temperature and reversible halochromic behaviour of these hydrogel films. Hence, the parameters such as concentrations of citric acid, reaction time and different pH values were varied individually to analyse their impact on the halochromic hydrogel film properties and their characterization using relevant instrumental techniques. This finding shows the results of the sample, successfully changing colour from yellow (pH 4) to violet (pH 6). Besides, the properties and characterization of crosslinker CMC-PEG films were discovered.